2011
DOI: 10.1242/dev.060988
|View full text |Cite
|
Sign up to set email alerts
|

BMP signaling orchestrates photoreceptor specification in the zebrafish pineal gland in collaboration with Notch

Abstract: SUMMARYA variety of signaling pathways have been shown to regulate specification of neuronal subtype identity. However, the mechanisms by which future neurons simultaneously process information from multiple pathways to establish their identity remain poorly understood. The zebrafish pineal gland offers a simple system with which to address questions concerning the integration of signaling pathways during neural specification as it contains only two types of neurons -photoreceptors and projection neurons. We h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(49 citation statements)
references
References 47 publications
(74 reference statements)
3
46
0
Order By: Relevance
“…In addition, Notch and BMP signaling pathways can block myogenic differentiation of C2C12 cells by regulating the expression of Hey1 through a direct interaction between Smad1 and NICD (50). In the zebrafish pineal gland, BMP signaling is a competence factor for Notch signaling to efficiently activate its target gene expression (51), whereas in the regulation of the initial formation of the olfactory nerve BMP signaling negatively affects Notch signaling to achieve the balance between the two pathways (52). In these two cases, it remains unclear how the two pathways are integrated.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Notch and BMP signaling pathways can block myogenic differentiation of C2C12 cells by regulating the expression of Hey1 through a direct interaction between Smad1 and NICD (50). In the zebrafish pineal gland, BMP signaling is a competence factor for Notch signaling to efficiently activate its target gene expression (51), whereas in the regulation of the initial formation of the olfactory nerve BMP signaling negatively affects Notch signaling to achieve the balance between the two pathways (52). In these two cases, it remains unclear how the two pathways are integrated.…”
Section: Discussionmentioning
confidence: 99%
“…Although we have learned a great deal concerning the role of Notch in vascular development from genetic manipulations in model systems, we still know little about when and where Notch is activated in endothelial cells during embryogenesis. We previously generated zebrafish lines that allow visualization of Notch-responsive cells and lineage tracing of progeny cells in which Notch has been activated (Clements et al, 2011;Lorent et al, 2010;Parsons et al, 2009;Quillien et al, 2011;Wang et al, 2011). In the study reported here, we have applied these transgenic lines together with genetic manipulation of Notch receptors and ligands, to investigate the dynamic role of Notch signaling during vascular development.…”
Section: Introductionmentioning
confidence: 99%
“…Although an increasing body of work has characterized the development of the pineal organ and the habenular nuclei in zebrafish (Masai et al, 1997;Cau and Wilson, 2003;Cau et al, 2008;Quillien et al, 2011), comparatively little attention has been lent to the formation of parapineal neurons. Previous work suggests that parapineal cells are likely to be specified prior to the 15-somite stage from a group of precursors in the anterior pineal complex anlage (Masai et al, 1997;Snelson et al, 2008a).…”
Section: Introductionmentioning
confidence: 99%
“…All pineal complex cell types undergo their final mitotic division in a similar time period between 15 and 24 hpf (Cau et al, 2008;Snelson et al, 2008b). The generation of the proper numbers of the different cell types (parapineal, pineal rod photoreceptor, pineal cone photoreceptor and pineal projection neuron) from the pineal complex anlage requires input from the Notch and Bmp pathways as well as the activity of at least two different transcription factors, T-box containing transcription factor 2b (Tbx2b) and the homeodomain-containing protein Floating head (Flh) (Masai et al, 1997;Cau et al, 2008;Snelson et al, 2008a;Snelson et al, 2008b;Quillien et al, 2011). However, additional genes are likely to be involved in cell specification in the pineal complex anlage, as a small number of parapineal and pineal neurons do form in tbx2b; flh double mutants (Snelson et al, 2008a).…”
Section: Introductionmentioning
confidence: 99%